Innovative Diagnostic Approaches and Treatment Strategies for Endometriosis: Current Trends and Future Direction - Review - Domino, Wiktoria; Śnieżna, Joanna; Florczak, Wojciech; Dzwonnik, Karol; Zelik, Urszula; Włodyka, Jagienka; Trestka, Gabriela; Przygoda, Maria; Dziewic, Jakub; Stępień, Kamila; et al. (Quality in Sport, 2025)
Endometriosis is a chronic gynecological condition affecting many women of reproductive age, often leading to infertility, pain, and other health issues. Diagnosing this disease is challenging due to its often nonspecific symptoms, and its diagnosis requires advanced imaging techniques and, in some cases, laparoscopy. This paper discusses current diagnostic methods used in endometriosis, such as ultrasonography, magnetic resonance imaging (MRI), and molecular tests. Treatment of endometriosis presents a significant medical challenge due to its chronic nature and the difficulty of managing it. The primary goals of treatment include pain relief, improving the patient’s quality of life, preventing disease recurrence, preserving fertility, and reducing the need for surgery. Depending on individual needs, various treatment methods are available, including pharmacological and surgical approaches. Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to alleviate symptoms, while hormonal therapies, such as combined oral contraceptives, GnRH agonists, and progestogens, aim to inhibit ovulation and estrogen production to reduce inflammation and slow disease progression. Surgery, typically laparoscopic, is indicated for severe symptoms or advanced disease. Innovative treatment methods show potential in managing endometriosis, but further studies are needed to confirm their safety and efficacy.